The urban revolution - Lefebvre, Henri (London University of Minnesota Press, 2003)
Originally published in 1970, The Urban Revolution marked Henri Lefebvre$1 (Bs first sustained critique of urban society, a work in which he pioneered the use of semiotic, structuralist, and poststructuralist methodologies in analyzing the development of the urban environment. Although it is widely considered a foundational book in contemporary thinking about the city, The Urban Revolution has never been translated into English$1 (Buntil now. This first English edition, deftly translated by Robert Bononno, makes available to a broad audience Lefebvre$1 (Bs sophisticated insights into the urban dimensions of modern life.s